PENERAPAN EKONOMI DIGITAL DAN EKONOMI HIJAU PADA PETANI JAMUR TIRAM KOPDAYA MINANG DI KOTA PADANG - Suhaemi, Zasmeli; Firdaus, Firdaus; Setiawan, Fadli; Mayuasti, Mayuasti (LPPM Universitas Andalas, 2025)
People who live in the Industry Era 4.0 are required not to be technology illiterate, including mushroom farmers in Padang. The purpose of this activity is to encourage mushroom farmers’ knowledge not only in applying digital economy technology for marketing but also in utilizing Oyster Mushroom waste as a potential economic resource to be marketed as the implementation of green economy. The target of this program is one of mushroom farmer communities that is called Kopdaya Minang. The approaches that have been treated are: 1) Socialization; 2) Training; and 3) Assistance and Evaluation of the related knowledge and skills. Transferring knowledge and training on processed Oyster Mushrooms and digital product marketing have been given to the target community as the implementation of digital economy. Moreover, it is continued by providing knowledge and training on utilization of Oyster Mushroom cultivation waste as the solid fertilizer for plant in the purpose of the application of green economy for oyster mushroom business. After training and assistance, the results of this program show mushroom farmers’ knowledge and skills are improved by 79,8%. There are three processed mushroom products (Crispy Mushrooms, Nuggets and Rendang), and three mushroom waste utilization products (fuel and fertilizers briquettes, and organic fertilizers), which are made of oyster mushroom waste have been produced. In conclusion, by having this activity makes oyster mushroom farmers’ knowledges and skills are increased, and the organic fertilizer which is made of mushroom waste and produced by the farmers has better quality than the National Standard.